The ERα membrane pool modulates the proliferation of pituitary tumours. Issue 2 (February 2019) - Sosa, Liliana del V; Petiti, Juan P; Picech, Florencia; Chumpen, Sabrina; Nicola, Juan P; Perez, Pablo; De Paul, Ana; Valdez-Taubas, Javier; Gutierrez, Silvina; Torres, Alicia I
Abstract : The molecular mechanisms underlying the ERα nuclear/cytoplasmic pool that modulates pituitary cell proliferation have been widely described, but it is still not clear how ERα is targeted to the plasma membrane. The aim of this study was to analyse ERα palmitoylation and the plasma membrane ERα (mERα) pool, and their participation in E2-triggered membrane-initiated signalling in normal and pituitary tumour cell growth. Cell cultures were prepared from anterior pituitaries of female Wistar rats and tumour GH3 cells, and treated with 10 nM of oestradiol (E2). The basal expression of ERα was higher in tumour GH3 than in normal pituitary cells. Full-length palmitoylated ERα was observed in normal and pituitary tumour cells, demonstrating that E2 stimulation increased both, ERα in plasma membrane and ERα and caveolin-1 interaction after short-term treatment. In addition, the Dhhc7 and Dhhc21 palmitoylases were negatively regulated after sustained stimulation of E2 for 3 h. Although the uptake of BrdU into the nucleus in normal pituitary cells was not modified by E2, a significant increase in the GH3 tumoural cell, as well as ERK1/2 activation, with this effect being mimicked by PPT, a selective antagonist of ERα. These proliferative effects were blocked by ICI 182780 and the global inhibitor of palmitoylation. These findings indicate that ERα palmitoylation modulated the mERα pool and consequently the ERK1/2 pathway, thereby contributing to pituitary tumour cell proliferation. These results suggest that the plasma membrane ERα pool might be related to the proliferative behaviour of prolactinoma and may be a marker of pituitary tumour growth.